2009
DOI: 10.1111/j.1747-7379.2009.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

What Determines the Embeddedness of Forced-Return Migrants? Rethinking the Role of Pre- and Post-Return Assistance

Abstract: Return migration is not always a process of simply “going home.” Particularly when return is not fully voluntarily, returnees face severe obstacles. This study argues that such return can only become sustainable when returnees are provided with possibilities to become re‐embedded in terms of economic, social network, and psychosocial dimensions. We analyze the return migration experiences of 178 rejected asylum seekers and migrants who did not obtain residence permit to six different countries: Afghanistan, Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 26 publications
3
118
0
6
Order By: Relevance
“…Their life stories, behaviours and frameworks of reference deviate from those of non-migrants, which potentially leads to alienation from the 'homeland' and its people (Ruben, van Houte, and Davids 2009). My interviews suggest that in Iraqi Kurdistan, this psychosocial struggle is closely tied with the weak rule of law.…”
Section: Psychosocial Reintegrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Their life stories, behaviours and frameworks of reference deviate from those of non-migrants, which potentially leads to alienation from the 'homeland' and its people (Ruben, van Houte, and Davids 2009). My interviews suggest that in Iraqi Kurdistan, this psychosocial struggle is closely tied with the weak rule of law.…”
Section: Psychosocial Reintegrationmentioning
confidence: 99%
“…KRG keeps no statistics, but by 2013, European Union member states had ordered over 95,000 Iraqis to return to Iraq (including Iraqi nationals other than Kurds), and roughly a third had complied or had been deported (Fandrich 2013, 16). In an interview with an official from the organisation, IOM confirmed that most of those who return through its assisted return programmes are Iraqi Kurds and that 21,507 individuals returned 'voluntarily' from Europe to Iraq during the period 2003-2012. Reintegration is complex and multidimensional, but central in the literature are its psychosocial and economic dimensions (Hammond 1999;King 2000;Ruben, van Houte, and Davids 2009). Each of these will be dealt with separately in the following analysis.…”
Section: Corruption and Returnee Reintegrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in spite of some excellent studies, including by Brotherton (2008), Brotherton and Barrios (2009), the Edmund Rice Centre (2006), Khosravi (2009), and Peutz (2006Peutz ( , 2010, relatively little is known about what happens to people in the months and years that follow deportation (Collyer 2012), that is, whether once removed they stay away, or whether other potential migrants are discouraged from migration. Whereas there is an established and expanding body of literature on what happens to people who decide to return to their countries of birth or previous residence (Dumon 1986;Hammond 1999;Arowolo 2000;Cassarino 2004;Hughes 2011) and on those returned as part of an INGO sponsored programme (Marsden 1999;Black, Collyer, and Somerville 2011), the work on those returned against their will is more limited, though growing (Ruben, Van Houte and Davids 2009). Given the claims made by states about the centrality of deportation to migration controls and to 'maintaining the integrity of the asylum system' (NAO 2005: 10), and the recommendation in the EU Returns Directive that there should be post-deportation monitoring, this lack of emphasis on what happens after forced return may seem surprising.…”
Section: Introductionmentioning
confidence: 99%
“…36 A number of studies describe the stigmatisation, socioeconomic marginalisation and alienation of returned sex workers in Benin City. 37 Consistent with such observations, returnees in our study describe the devaluation of social capital upon return.…”
Section: Post-return: the Vulnerabilities Of Victims Of Trafficking Bmentioning
confidence: 99%